Interplay between the genetic clades of Micromonas and their viruses in the Western English Channel. Issue 5 (23rd July 2015) - Baudoux, A.‐C.; Lebredonchel, H.; Dehmer, H.; Latimier, M.; Edern, R.; Rigaut‐Jalabert, F.; Ge, P.; Guillou, L.; Foulon, E.; Bozec, Y.; Cariou, T.; Desdevises, Y.; et al.
Summary The genus Micromonas comprises distinct genetic clades that commonly dominate eukaryotic phytoplankton community from polar to tropical waters. This phytoplankter is also recurrently infected by abundant and genetically diverse prasinoviruses. Here we report on the interplay between prasinoviruses and Micromonas with regard to the genetic diversity of this host. For 1 year, we monitored the abundance of three clades of Micromonas and their viruses in the Western English Channel, both in the environment using clade‐specific probes and flow cytometry, and in the laboratory using clonal strains of Micromonas clades to assay for their viruses by plaque‐forming units. We showed that the seasonal fluctuations of Micromonas clades were closely mirrored by the abundance of their corresponding viruses, indicating that the members of Micromonas genus are susceptible to viral infection, regardless of their genetic affiliation. The characterization of 45 viral isolates revealed that Micromonas clades are attacked by specific virus populations, which exhibit distinctive clade specificity, life strategies and genetic diversity. However, some viruses can also cross‐infect different host clades, suggesting a mechanism of horizontal gene transfer within the Micromonas genus. This study provides novel insights into the impact of viral infection for the ecology and evolution of the prominent phytoplankter Micromonas.